Healthy eating: Portugal’s proposal to improve health through public health - Salomão, Devani (Seven Editora, 2024)
This reflection is the result of the analysis of two Biannual Progress Reports that refer to the Integrated Strategy for the Promotion of Healthy Eating - EIPAS, which establishes as a priority "to promote health through Public Health, assuming as fundamental the policy of promoting healthy eating" (Order No. 11.418/2017, 29/12/2017). Inadequate eating habits are one of the main risk factors for early mortality in the Portuguese population. Chronic non-communicable diseases (NCDs) - cardiovascular, diabetes, obesity and oncological - are diseases with a high prevalence in the Portuguese population, with cardiovascular diseases being the main cause of death in the country. The aim was to expand the evidence related to healthy eating policy and form a basis for more specific future research. Methodology: field research and bibliographic sources, as well as content analysis of two reports. Results: In the content analysis, the categories that appear most often are "healthy eating", "communication" and "public administration". We observed the preponderance of the subject "healthy eating" in the texts of the reports. Communication had good emphasis. It is inferred that the Ministry of Health (public administration) intends to try to establish a common point in the narratives between experts and citizens, so that people can better understand and thus be able to decide on what is recommended in the various aspects of healthy eating and health, both in the material analyzed and in other media. DOI:https://doi.org/10.56238/sevened2024.018-022